Formação continuada em educação física e inclusão do deficiente no ensino regular sob a ótica de professores =: The ongoing graduation in physical education studies and the inclusion of disable people in regular schools under the teacher's perception - Tebaldi, Marina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This current investigation focuses on analyzing municipal school teachers’ perception in Rio Claro city, State of São Paulo. It concerns the continuing education in Physical Education studies and the inclusion of disabled students in regular schools. It is about qualitative research and in the literature review, issues referred to continuing education, inclusion and inclusive education have been approached. Through semi structured interviews, four declarations have been given by municipal school teachers in Rio Claro/SP and another one was given by the teaching coordinator of Special Education. The information collected in the interviews has been analyzed through Content Analysis Technique. Favorable declarations regarding ongoing graduation contributions in inclusive perspective have been verified. They have supported teachers in the difficult pedagogic task referred to disabled students’ inclusion in Regular Education. Nevertheless, multidisciplinary work is not performed yet and there is lack of materials and resources, in other words, there is lack of adequate physical facilities. Besides the Public Policy Programs offered by the City Hall to municipal teachers, it is necessary to provide courses with emphasis on inclusive themes such as specific ones regarding scientific terms and the pedagogical intervention in the field of intellectual and motor disabilities. Otherwise, what is determined by laws as well as approached by experts in this field will be hardly corresponded. It was concluded that for inclusive continuing education for teachers to be effective, there must be a multidisciplinary work, meeting all the needs of the students, an ongoing education designed by teachers, and performed with the aid of the same

A presente investigação objetivou analisar a percepção de um de grupo de professores, da Rede Municipal de Ensino da cidade de Rio Claro-SP, no que diz respeito à Formação Continuada em Educação Física e à inclusão do deficiente no Ensino Regular. Trata-se de pesquisa qualitativa e na revisão da literatura abordaram-se os temas referentes à formação continuada, deficiências e inclusão. Por intermédio da técnica de entrevista semiestruturada foram coletados oito depoimentos de professores da Rede Municipal de uma cidade do interior paulista e um da professora coordenadora da Educação Especial. Os dados provenientes das entrevistas foram analisados em conformidade com a técnica de Análise de Conteúdo Temático. Constataram-se depoimentos favoráveis às contribuições da formação continuada na perspectiva da inclusão do deficiente e vêm auxiliando o professor na difícil questão pedagógica referente à inclusão do educando deficiente no Ensino Regular. Entretanto, um trabalho multidisciplinar ainda não é efetuado e há falta de materiais e recursos, ou seja, de infraestrutura física adequada, e os cursos de formação nesta perspectiva inclusiva ainda são básicos. Não obstante à existência de políticas públicas da Prefeitura Municipal oferecidas ao professor escolar, urge a realização de mais cursos com ênfase à temática inclusiva, bem como, específicos em termos de conhecimentos científicos e da intervenção pedagógica no campo das deficiências intelectuais e motoras. Caso contrário, dificilmente o que é determinado por leis, bem como, abordado por estudiosos nesta área, será concretamente aplicado. Concluiu-se que, para que a formação continuada inclusiva seja eficaz para os professores, deve existir um trabalho multidisciplinar, atendendo todas as necessidades dos educandos, uma formação continuada pensada pelos professores, e realizada para atender as necessidades desses professores
Keywords: Teachers, Training of; Professores - Formação; Educação inclusiva; Inclusão em educação; Ensino; Ensino - Curriculos; Educação física para deficientes